2013
DOI: 10.1007/s12105-013-0447-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EGFR, VEGF, and NOTCH1 Suggest Differences in Tumor Angiogenesis in HPV-Positive and HPV-Negative Head and Neck Squamous Cell Carcinoma

Abstract: There is current interest in anti-angiogenesis therapies for head and neck squamous cell carcinomas (HNSCC), although the utility of these therapies in human papillomavirus (HPV) positive and HPV-negative HNSCC is unclear. Therefore, we explored heterogeneity in expression of a distal factor in angiogenesis (EGFR, the epidermal growth factor receptor), a proximal factor in angiogenesis (VEGF, the vascular endothelial growth factor) and a putative factor in angiogenesis (NOTCH1) in a HNSCC case series using imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
(69 reference statements)
3
25
0
Order By: Relevance
“…RPPA analyses revealed that HPV(+) OPSCC expressed lower levels of EGFR (Figure 1A and Table 2) and, although not significant, had decreased expression of activated EGFR (EGFR pY1173, p = 0.05, and EGFR pY992, p = 0.07, Supplemental Table 1). These data support described inverse correlation between HPV-positivity and EGFR expression (20). Downstream targets of EGFR activity were also expressed at relatively lower levels in HPV(+) compared to HPV(−) tumors, including STAT3 and activated MEK1/2 (phospho-S217).…”
Section: Resultssupporting
confidence: 89%
“…RPPA analyses revealed that HPV(+) OPSCC expressed lower levels of EGFR (Figure 1A and Table 2) and, although not significant, had decreased expression of activated EGFR (EGFR pY1173, p = 0.05, and EGFR pY992, p = 0.07, Supplemental Table 1). These data support described inverse correlation between HPV-positivity and EGFR expression (20). Downstream targets of EGFR activity were also expressed at relatively lower levels in HPV(+) compared to HPV(−) tumors, including STAT3 and activated MEK1/2 (phospho-S217).…”
Section: Resultssupporting
confidence: 89%
“…The association between EGFR overexpression and HPV-negative, but not HPV-positive, HNSCC has been reported previously 32-35 . Our data also showed similar results (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…The impact of HPV status on response to cetuximab therapy is incompletely understood. Others reported that endogenous expression of the HPV oncogenes in vitro did not significantly impact response to EGFR inhibition, and response rates to cetuximab in patients with HPV[+] and HPV[−] HNSCC were similar (9). However, cetuximab is rarely administered in the clinic as a monotherapy (26), thus evaluating the direct relationship between HPV status and response to cetuximab therapy has been challenging.…”
Section: Discussionmentioning
confidence: 99%
“…HPV oncogenes have not been shown to modulate the anti-EGFR antibody responses in HNSCC (6, 8). Others have found that EGFR is selectively overexpressed in HPV[−] HNSCC (9). HER2 and HER3 have been associated with other HPV-associated cancers (10, 11).…”
Section: Introductionmentioning
confidence: 99%